Changes in gene expression of Prymnesium parvum induced by nitrogen and phosphorus limitation - Liu*, Zhenfeng; Koid*, Amy E.; Terrado, Ramon; Campbell, Victoria; Caron, David A.; Heidelberg, Karla B. (Frontiers in Microbiology, 2015)
Prymnesium parvum is a globally distributed prymnesiophyte alga commonly found in brackish water marine ecosystems and lakes. It possesses a suite of toxins with ichthyotoxic, cytotoxic and hemolytic effects which, along with its mixotrophic nutritional capabilities, allows it to form massive Ecosystem Disruptive Algal Blooms (EDABs). While blooms of high abundance coincide with high levels of nitrogen (N) and phosphorus (P), reports of field and laboratory studies have noted that P. parvum toxicity appears to be augmented at high N:P ratios or P-limiting conditions. Here we present the results of a comparative analysis of P. parvum RNA-Seq transcriptomes under nutrient replete conditions, and N or P deficiency to understand how this organism responds at the transcriptional level to varying nutrient conditions. In nutrient limited conditions we found diverse transcriptional responses for genes involved in nutrient uptake, protein synthesis and degradation, photosynthesis, and toxin production. As anticipated, when either N or P was limiting, transcription levels of genes encoding transporters for the respective nutrient were higher than those under replete condition. Ribosomal and lysosomal protein genes were expressed at higher levels under either nutrient-limited condition compared to the replete condition. Photosynthesis genes and polyketide synthase genes were more highly expressed under P-limitation but not under N-limitation. These results highlight the ability of P. parvum to mount a coordinated and varied cellular and physiological response to nutrient limitation. Results also provide potential marker genes for further evaluating the physiological response and toxin production of P. parvum populations during bloom formation or to changing environmental conditions.